1976
DOI: 10.7326/0003-4819-84-2-181
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid Liver Injury: Clinical Spectrum, Pathology, and Probable Pathogenesis

Abstract: The clinical spectrum of isoniazid-induced liver injury seems to be clinically, biochemically, and histologically indistinguishable from viral hepatitis, except that the injury occurs primarily in persons older than 35 years. A possible relation between susceptibility of patients to isoniazid liver injury and rapid metabolism (acetylation) of the drug has been found. Examination of isoniazid metabolites showed that patients with rapid acetylator phenotype hydrolyze much more isoniazid to isonicotinic acid and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
292
1
5

Year Published

1977
1977
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 469 publications
(303 citation statements)
references
References 27 publications
5
292
1
5
Order By: Relevance
“…The elderly appear to be vulnerable to antituberculosis drugs. 5,6,[12][13][14][15] Nevertheless, after adjustment for age, we found that CYP2E1 remained a significant independent risk factor for antituberculosis drug-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The elderly appear to be vulnerable to antituberculosis drugs. 5,6,[12][13][14][15] Nevertheless, after adjustment for age, we found that CYP2E1 remained a significant independent risk factor for antituberculosis drug-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 76%
“…10,[13][14][15][16][17] Alcohol consumption, advanced age, acetylator status, and existing chronic liver disease have been reported to increase the risk of antituberculosis drug-induced hepatitis. [3][4][5][6][7][8][9][10][11][12][13][14][15] However, the exact mechanism for this hepatotoxicity remains unclear.…”
mentioning
confidence: 99%
See 3 more Smart Citations